Spicing up endogenous neural stem cells: aromatic-turmerone offers new possibilities for tackling neurodegeneration - Poser, Stephen W.; Androutsellis-Theotokis, Andreas (American Diabetes Association, 2014)
There is a growing interest in the therapeutic utility of compounds derived from Curcuma longa, an herb of the Zingiberaceae family that has been part of traditional medicine for centuries. Recent reports suggest that bioactive compounds isolated from the rhizome of these plants can address two key aspects of brain injury following stroke that must be dealt with for functional recovery to occur: the moderation of neuroinflammation, and the mobilization of endogenous stem cells resident in the nervous system. Defining their mechanism of action remains a question, but emerging evidence may point towards one shared with more classic modulators of neural stem cell proliferation and survival.